Hybridization of signaling principle and Nielsen's design guideline in a mobile application - Arifah Fasha, Rosmani (2022)
Many educational mobile applications available in the market use multimedia principles in several aspects. However, the user interface design component is often disregarded. Therefore, such applications are less effective in engaging users in learning content with excitement and motivation. Therefore, this project is being worked on to meet those needs. A study on mobile applications hybridized with the Signaling principle and Nielsen guidelines through the construction of the NSPIxD model was carried out. Two mobile applications were designed, developed, and evaluated, and the Alessi and Trollip Instructional Design Models were adapted in both applications. The first mobile application, AHMA-0, serves as the base model. Instead, the AHMA-NSPIxD is integrated with the NSPIxD model, accompanied by a hybridization of the Signal principles and Nielsen design guidelines. Three parameters were measured, evaluated, and compared between AHMA-0 and AHMA-NSPIxD. The relevant parameters are; students’ knowledge and awareness of the topic and student motivation to use learning materials on the subject. It was found that AHMA-NSPIxD outperformed AHMA-0. Accordingly, it proves that practical applications can be produced at all levels by considering users' needs. Further, these findings emphasize the importance of critically considering user interfaces' technical and aesthetic aspects, contributing to advancing interaction design knowledge.